THE EFFECTS OF ENGLISH VIDEO CLIPS WITH PEER SUPPORT ON YOUNG LEARNERS’ ORAL READING SKILL - Asnawi Asnawi; Zulfadli A. Azis; Nora Fitriani (Center of Language and Cultural Studies [CLCS], 2016)
The study reports the effects of English video clips with and without peer support on young learners’ oral reading production skill. Using quasi experiment with pre-and-post test design, this study assigned 44 students of SMPN 8 Banda Aceh selected at random. The sample was divided into two groups each of which received the same video clips downloaded from YouTube. Group one worked with peer support on their own choice partners and group two worked without peer support. Tape recorder was used in the pre and posttest to record students’ oral reading skill. To analyze the data, one way ANOVA was used. The result found that the peer support strategy significantly improved oral production in reading for phrasing, pausing, stressing, intonation, and rate. In summary, English video clips with peer support improves oral reading production.